Terahertz wireless communication using GaAs transistors as detectors. Issue 4 (1st February 2014) - Tohmé, L.; Blin, S.; Ducournau, G.; Nouvel, P.; Coquillat, D.; Hisatake, S.; Nagatsuma, T.; Pénarier, A.; Varani, L.; Knap, W.; Lampin, J.‐F.
Abstract : The detection of high data‐rate wireless communication using a terahertz‐frequency carrier, and a GaAs transistor as a detector, is reported. Communications are investigated around 0.2 and 0.3087 THz. For the first time, an error‐free transmission at data rates up to 8.2 Gbit/s is demonstrated, using a carrier frequency of 0.3087 THz.